Transformation of Learning Leadership in the Digital Era: A Qualitative Analysis Based on Literature Studies on Adaptive Educational Management Models - Nurjanah Nurjanah (Journal of Dialogos, 2025)
This study aims to analyze the transformation of learning leadership in the digital era through a qualitative literature review to identify the characteristics of adaptive educational management models. Technological dynamics require educational leaders to possess digital literacy capacity, strategic sensitivity to change, and the ability to integrate digital tools into managerial and pedagogical processes. The literature review indicates that transformational and distributive leadership models offer a strong conceptual foundation for creating a culture of innovation, collaboration, and evidence-based decision-making. The analysis also found that the success of digital transformation is influenced by organizational readiness, policy structures, and the quality of professional relationships between stakeholders. Institutions that are able to adapt effectively demonstrate a pattern of continuous capacity development, are responsive to technological risks, and consistently balance technical and ethical aspects. The synthesis of various findings shows that adaptive learning leadership focuses not only on technological mastery but also on the ability to create a flexible, collaborative, and quality-oriented educational ecosystem. The results of this study emphasize the importance of educational leaders who are visionary, innovative, and able to guide institutions through digital change in a directed and sustainable manner, so that educational management remains relevant and competitive in the modern era